2020
DOI: 10.1186/s12886-020-01649-w
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium haemophilum scleritis: two case reports and review of literature

Abstract: Background Mycobacterium haemophilum is a rare and emerging nontuberculous mycobacteria (NTM). It normally causes localized or disseminated systemic diseases, particularly skin infections and arthritis in severely immunocompromised patients. There have been 5 cases of M. haemophilum ocular infections reported in the literature. Only 1 case presented with scleritis with keratitis. Here, we reported 2 cases of M. haemophilum scleritis. One of them was immunocompetent host and had keratitis with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Tender, erythematous nodules and papules overlying joints on extremities that progress to painful draining abscesses and ulcers as seen in our patient are most common 6 8 10 12 18. Arthritis and osteomyelitis are also common, with less common sites of infection being the lungs, lymph nodes, eyes and the central nervous system (CNS) 4 7–9 12 14…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Tender, erythematous nodules and papules overlying joints on extremities that progress to painful draining abscesses and ulcers as seen in our patient are most common 6 8 10 12 18. Arthritis and osteomyelitis are also common, with less common sites of infection being the lungs, lymph nodes, eyes and the central nervous system (CNS) 4 7–9 12 14…”
Section: Discussionmentioning
confidence: 60%
“…The exact prevalence as a pathogen is likely underreported due to these unique growth requirements 6 10. Since it was first recognised by Sompolinsky et al 11 in 1978 as a cause of generalised skin granulomata and subcutaneous abscesses in a patient receiving immunosuppressive therapy for Hodgkin’s disease, there have been approximately 300 cases reported, almost always in patients who are immunosuppressed 3–15. The underlying immunosuppression in patients with M. haemophilum infections has historically been advanced HIV, haematological malignancy or bone marrow transplant.…”
Section: Discussionmentioning
confidence: 99%
“…These 12 articles, which describe a total of 37 immunocompetent adults between 2002 and 2021, are summarized in Table 1. [8][9][10][11][12][13][14][15][16][17][18][19] These cases were identified in USA, Canada, Germany, Switzerland, Thailand, China and Singapore.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Of the 601 remaining papers, 144 articles reported on M. haemophilum infection in immunocompromised patients, 21 reported infection in children, and 12 reported infection in immunocompetent adults (Figure 3). These 12 articles, which describe a total of 37 immunocompetent adults between 2002 and 2021, are summarized in Table 1 8–19 . These cases were identified in USA, Canada, Germany, Switzerland, Thailand, China and Singapore.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Pisitpayat et al reported two cases of Mycobacterium haemophilum infection, of which the first was in an immunocompromised individual and presented with multiple pustular lesions. [ 41 ] The second case presented with nodular scleritis with keratouveitis and radial keratitis.…”
Section: Scleritismentioning
confidence: 99%